OUTCOME OF ARTHROSCOPIC NON-ANATOMIC REPAIR OF MASSIVE ROTATOR CUFF TEAR: A RETROSPECTIVE ANALYSIS - Usama, Muhammad; uddin, Bilal; Umer Faheem, Muhammad; Amin, Asad; Ahmed Bajwa, Mubashar; Sohail, Ayesha; Ahmad Khan, Shaheryar (Journal of Ayub Medical College Abbottabad, 2024)
Background: The aim was to assess the clinical outcome of non-anatomic rotator-cuff repair in large tears not amenable to anatomic repair and to assess the preoperative factors that affect the result of such repairs. A retrospective case-series at Ghurki Trust Teaching Hospital, Lahore. Twenty-seven cases that underwent non-anatomic rotator-cuff repair at GTTH over the last 5 years and met inclusion criteria were assessed over a three-month study period (from 01/10/2023 to 31/12/2023). Methods: Outcome was assessed in terms of improvement in pain as per visual-analog-scale (VAS), UCLA, as well as Constant score. Furthermore, patients’ satisfaction was also assessed to measure subjective efficacy of the procedure. Results: Most commonly cases of rotator cuff tear present with pain, weakness, and restriction of shoulder range of motion. Pain improved significantly (p<0.001) from preoperative score of 3.68 to 1.45. Analysis of the objective assessment showed statistically significant (p=001) improvement in Constant score from a preoperative average score of 63.63 to a postoperative average of 77.27, with significant improvement (p=0.05) in each individual scoring criteria as well. The other scoring studied: UCLA also improved significantly (p=0.001) from 25.36 to 30.18. Despite this, on subjective assessment 40.9% of the sample was very satisfied and 27.3% were satisfied with the outcome. Conclusion: Non-anatomic repair is very effective at treating the presenting complaints of the rotator cuff tear patients. Thus, alongside good clinical outcome, patient satisfaction can be predicted after the procedure.